Measuring the effectiveness of the temporal dominance of sensations technique to investigate the dynamic perception of oral nutritional supplements by older adults. (March 2023) - Regan, E.; Feeney, E.L.; Schlich, P.; Hutchings, S.C.; O'Neill, G.J.; O'Riordan, E.D.
Highlights: Older adults could effectively discriminate between four ONS of varying viscosities. Low viscosity ONS induced little differences in dynamic perception. High viscosity ONS induced clear differences in dynamic perception. Older adults preferred high viscosity ONS to younger adults. TDS is suitable for dynamic evaluations of beverages with older adults. Abstract: To develop nutritional beverages for older adults, understanding their dynamic sensory perception is vital. Limited research has used Temporal Dominance of Sensations (TDS) methodology to evaluate the dynamic perception of beverages with older adults. Therefore, this study sought to measure the effectiveness of the TDS methodology to investigate the differences in dynamic perception by older adults across a range of texturally modified Oral Nutritional Supplements (ONS). Thirty-five older adults (65+ years) evaluated four ONS of differing viscosities ranging from low (0.009 Pa.s at 50 s −1 ) to high viscosity (0.177 Pa.s at 50 s −1 ) over one 30-minute session. For each ONS, a 45 mL volume was consumed, over three 15 mL sips. Panellists evaluated each sip over 40 seconds. Liking was also measured using a 9-point hedonic scale. To make a judgement on older adult's use of the method, a younger cohort of volunteers (18–35 years) also completed the beverage evaluation as a benchmark. Older adults indicated 3.9 dominances, based on 2.8 attributes, and waited 22 seconds before selecting their first attribute. No differences in average dominance durations were apparent with age. Furthermore, older adults generated clear TDS curves and effectively used the TDS task to discriminate between the four texturally modified ONS. Some similarities in dominant attributes were apparent across older and younger cohorts. This study enhanced our understanding of how older adults utilise the TDS technique to evaluate liquid type products. The study showed that the TDS technique is suitable for use with older adults.